Effect of its Mechanical Properties on Concrete Mix were sand is Partially Replaced with Industrial Ash - Anant Kumar, Krishna Deep, Anita Chaturvedi, Sarika Ghamforia (Mathematical Statistician and Engineering Applications, 2023)
In this present era, the use of alternative material and utilization of several types of waste is a very common topic. Now a day’s using an alternative material and recycled waste material for the manufacturing of new product and this area is rapid growing day by day and with recent and innovative techniques. Reuse and recycled the waste material can be beneficial for the environment point and also it enhances the efficiency and durability is some aspect. In the field of concrete, various technological changes occur every day. Construction industry also encourages such technological changes and try to utilize the alternate product in place of conventional material. The conventional material are now very limited in quantity which can be depleted day by day and also due to its excess use can create various types of environment effects in the nature. This problem has bought the option of use of alternative sand. In the present study and laboratory test an attempt has made to use fly ash (which is a by-product coming from thermal power plants) as alternative raw material for our project and which is removed in some percentage of sand. The properties of these alternative sands are determined with the help of mechanical investigation such as slump test, compaction factor test and compressive strength test and compared with Natural sand. These sands can be used in place of natural sand. The use of these alternative sand is cost effective and eco- friendly.